Analisis Yuridis Terhadap Pembuatan Akta Hibah Sebagai Alat Bukti Dalam Sengketa Kepemilikan Tanah - Cyntia Marshel, Dwi (Recital Review, 2025)
A deed of grant (akta hibah) is an authentic legal instrument used to prove the transfer of land and building ownership from a donor to a recipient without compensation. Although grants are regulated under the Indonesian Civil Code, the Basic Agrarian Law, and land registration regulations, in practice many grants are still executed through private deeds or remain unregistered, often leading to ownership disputes. This gap between legal provisions and implementation forms the basis of this study, which examines the juridical aspects of grant deeds and their evidentiary strength in land disputes. The findings reveal that a properly executed grant deed, fulfilling both formal and material requirements before a Land Deed Official (PPAT) and registered with the Land Office, holds perfect evidentiary value as an authentic deed. Conversely, improperly executed deeds may be annulled, as demonstrated in several court rulings on disputed grants. This study contributes to legal scholarship by emphasizing the importance of procedural compliance and the crucial role of PPAT in ensuring legal certainty, protecting parties’ rights, and preventing potential family conflicts in the future.